Berthe Morisot - Higonnet, Anne, 1959-; Morisot, Berthe, 1841-1895 (Berkeley : University of California Press, 1995)
Of the six Impressionist painters whose first exhibition scandalized and fascinated Paris in 1874, Berthe Morisot was the only woman. She reached a pinnacle of artistic achievement despite the restraints society placed on her sex, adroitly combining her artistic ambitions with a rewarding family life. Anne Higonnet brings fully to life an accomplished artist and her world.
Preface -- 1. Family background 1841-1857 -- 2. First lessons 1857-1867 -- 3. Contacts 1859-1967 -- 4. Encounters and partings 1868-1869 -- 5. Alternatives 1869-1971 -- 6. Political Crisis 1870-1871 -- 7. Personal crisis 1870-1872 -- 8. Resolutions 1872-1874 -- 9. Joining the impressionist movement 1873-1874 -- 10. First impressionist exhibition 1874 -- 11. Eugene Manet -- 12. Artistic events -- 13. New bond -- 14. Impressionism comes of age -- 15. Fulfillment 1878-1883 -- 16. Loss 1883-1886 -- 17. La Grande dame de la Peinture 1884-1891 -- 18. Art closer to home and farther abroad 1885-1891 -- 19. Bereavement and acclaim 1892-1894 -- 20. Summation 1895.
Originally published: New York : Harper & Row, 1990.
Includes bibliographical references (page 231) and index.
English.
Print version record.
eBooks on EBSCOhost
Keywords: Morisot, Berthe, -- 1841-1895.; Morisot, Berthe, -- 1841-1895; Artists -- France -- Biography; Human rights; Ethnic groups; Medical personnel; Social psychology; Psychology, Applied; Social sciences; Mental health services; Health services administration; Diseases; Social problems; Humanities; Crime; Social control; National health services; Obstetrics -- Surgery; Reproductive technology; Mental illness; Criminology; Sociology; Philosophy; Medical care; Anatomy; Pregnancy -- Complications; Race; Therapeutics; Economics; Surgery, Operative; Steroids; Polycyclic compounds; Drugs; Prejudices; People with disabilities; Eugenics; Violence; Women's rights; Contraception; Drug abuse; Drug addiction; Women's health services; Mifepristone; Physicians; Women; African Americans; Politics, Practical; Pregnant women; History; Pregnancy; Psychology; Government aid; Federal aid; Abortion; Fetus; Ethics; Behavioral Sciences; Human Rights; History, Modern 1601-; Ethnicity